Status of the laboratory infrastructure for detector calibration and characterization at the European XFEL. (20th December 2016) - Raab, N.; Ballak, K.-E.; Dietze, T.; Ekmedzič, M.; Hauf, S.; Januschek, F.; Kaukher, A.; Kuster, M.; Lang, P.M.; Münnich, A.; Schmitt, R.; Sztuk-Dambietz, J.; et al.
Abstract: The European X-ray Free Electron Laser (XFEL.EU) will provide unprecedented peak brilliance and ultra-short and spatially coherent X-ray pulses in an energy range of 0.25 to 25 keV . The pulse timing structure is unique with a burst of 2700 pulses of 100 fs length at a temporal distance of 220 ns followed by a 99.4 ms gap. To make optimal use of this timing structure and energy range a great variety of detectors are being developed for use at XFEL.EU, including 2D X-ray imaging cameras that are able to detect images at a rate of 4.5 MHz, provide dynamic ranges up to 10 5 photons per pulse per pixel under different operating conditions and covering a large range of angular resolution \cite{requirements, Markus}. In order to characterize, commission and calibrate this variety of detectors and for testing of detector prototypes the XFEL.EU detector group is building up an X-ray test laboratory that allows testing of detectors with X-ray photons under conditions that are as similar to the future beam line conditions at the XFEL.EU as is possible with laboratory sources [1]. A total of four test environments provide the infrastructure for detector tests and calibration: two portable setups that utilize low power X-ray sources and radioactive isotopes, a test environment where a commercial high power X-ray generator is in use, and a pulsed X-ray/electron source which will provide pulses as short as 25 ns in XFEL.EU burst mode combined with target anodes of different materials. The status of the test environments, three of which are already in use while one is in commissioning phase, will be presented as well as first results from performance tests and characterization of the sources.